Sustainable and flexible human resource management for innovative organizations (2017)
In response to the changes in economies and technology in recent decades, research in organizational theories have been focused toward innovative and entrepreneurial organizations. A research issue in this evolving research endeavor is adaptation of human resource management and the establishment of a sustainable human resource management. This paper investigates the main characteristics of a sustainable HRM in innovative organizations. The aim is to identify sustainable HRM as a key toward competing in turbulent markets. The problem statement is to find the relationship between psychological capital, HR flexibility and sustainable HRM in innovative organizations. Three main variables of HR flexibility, HR sustainability and psychological capital form the theoretical model of this study; and four hypotheses are developed based on this model. Findings do not reject any of four hypotheses, so it is concluded that psychological capital and HR flexibility has positive and meaningful effect on sustainable HRM; and in addition, psychological capital has positive and meaningful effect on sustainable HRM. Moreover, flexibility has moderate role in relationship between psychological capital and sustainable HRM